Solvent Effects on One- and Two-Photon Optical Properties of a Novel 2, 2':6', 2''-Terpyridine-Based Chromophore (Journal of Atomic and Molecular Sciences, 2013)
At ab initio level, time-dependent hybrid density functional theory and responsetheory have been applied to study the solvent effect on the geometrical andelctronic structure as well as one- and two-photon absorption (TPA) properties of2,2':6',2"-terpyridine-based chromophore L. It is found that solvatochromic shift ofcharge-transfer (CT) appears nonmonotonic behavior with regard to the polarity ofsolvent. Besides, the one-photon absorption (OPA) strengths are enlarged slightly andare more dependent on the optical dielectric constant. The TPA cross sections are enhancedwhen considering solvent effect compared to that in gas phase and the TPAcross sections show an increasing trend with the increase of solvent polarity. All thetheoretical results are in reasonable agreement with experimental data.
Keywords: solvent effect; two-photon absorption; response theory; organic compound.